A Comparative Study between Agile Methods of Software Development - Humberto Rocha de Almeida Neto; Edviges Mariza Campos de Magalhães; Alexandre J. H. de O. Luna; Hermano Perrelli de Moura; Bruno N. Figueiredo; Felipe A. A. Ramalho; Felipe D. Alves; Thiago R. Santos (Anais do Encontro Anual de Tecnologia da Informação, 2012)
Agile methods are being more and more used to develop systems to meet requirements such as agility, efficiency and better response to changes. On the other hand, we now have a considerable range of options that, despite being based on the principles of the agile manifesto, may offer distinct features and applicability. In this article we will present an extension of comparative studies between Agile Methods with the aim of spreading such methods and to assist organizations in adopting agile practices.